Pengaruh Pemberian Pupuk Organik Cair Rebung Bambu Terhadap Pertumbuhan Tanaman Kubis Bunga (Brassica oleracea var. botrytis L.) - Dwi Wulandari; Nanik Lutfiyah; Anisa Arianti (KAMBIUM Jurnal Pertanian, 2026)
Cauliflower (Brassica oleracea var. botrytis L.) is a vegetable belonging to the cruciferous family. This plant has high economic value and relatively stable market demand. The purpose of this study was to determine the effect of liquid organic fertilizer doses from bamboo shoots on the growth and yield of cauliflower (Brassica oleracea var. botrytis L.). The research method used is RAK with 6 treatments and 4 replications. The treatments are as follows P0 = 0 ml / L water (without treatment), P1 = 4 grams / L NPK water, P2 = 50 ml / L bamboo shoot POC water, P3 = 100 ml / L bamboo shoot POC water, P4 = 150 ml / L bamboo shoot POC water, P5 = 200 ml / L bamboo shoot POC water. This research was conducted in October - December 2024. The experimental location was in Dsn. Banyuurip Rt 001 / RW 001, Ds. Mundusewu, Bareng District, Jombang Regency, East Java with an altitude of ± 500 m. The parameters observed included plant height, number of leaves, plant wet weight, plant flower weight, mass weight per unit. The data analysis used ANOVA (Analysis of Variance) with Honestly Significant Difference (HSD) test at 5% level. The results of this study indicate that the treatment of liquid organic fertilizer from bamboo shoots significantly affects the growth and yield of cauliflower (Brassica oleracea var. botrytis L.). The optimal dose is between 150-200 ml/L on the parameters of plant height, number of leaves, flower weight, fresh weight and flower mass weight per plant on cauliflower plants.